1992
DOI: 10.1104/pp.98.4.1386
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Abscisic Acid Synthesis

Abstract: When applied to young nondormant embryos of sunflower (Helianthus annus) (7-10 day[s] after pollination [DAP]), abscisic acid (ABA) inhibited germination as long as it was present. However, whatever the dose used and the duration of its application, ABA was unable to induce dormancy because after transfer of treated embryos to control (without ABA) medium, germination occurred. Thereafter, exogenous ABA became effective and allowed the dormancy to develop in 13 and 17 DAP embryos, i.e. in embryos which after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(21 citation statements)
references
References 10 publications
(16 reference statements)
2
18
0
Order By: Relevance
“…The effect of inhibiting ABA synthesis in sorghum is consistent with current knowledge about the role of ABA in the onset of dormancy; ABA-deficient mutants Days After Pollination of tomato and Arabidopsis thaliana both have very low levels of dormancy (Karssen et al, 1983;Groot and Karssen, 1992). Lowering ABA levels with fluridone has been shown to reduce dormancy in maize (Fong et al, 1983) and sunflower (Le Page-Degivry et al, 1992) seeds. In addition, changes in dormancy produced by fluridone could, to a certain extent, be related to its effects on embryonic sensitivity to ABA (Fig.…”
Section: I Sc U Sslonsupporting
confidence: 79%
See 1 more Smart Citation
“…The effect of inhibiting ABA synthesis in sorghum is consistent with current knowledge about the role of ABA in the onset of dormancy; ABA-deficient mutants Days After Pollination of tomato and Arabidopsis thaliana both have very low levels of dormancy (Karssen et al, 1983;Groot and Karssen, 1992). Lowering ABA levels with fluridone has been shown to reduce dormancy in maize (Fong et al, 1983) and sunflower (Le Page-Degivry et al, 1992) seeds. In addition, changes in dormancy produced by fluridone could, to a certain extent, be related to its effects on embryonic sensitivity to ABA (Fig.…”
Section: I Sc U Sslonsupporting
confidence: 79%
“…Tomato (Groot et al, 1991), Arabidopsis (Karssen et al, 1983), and maize (Neill et al, 1987) mutants deficient in ABA synthesis show substantially reduced peak ABA contents and almost no dormancy. Accordingly, the inhibition of ABA synthesis during early development of maize seeds blocks their entrance into dormancy (Fong et al, 1983), and the inclusion of fluridone in the incubation medium stimulates the germination of dormant sunflower embryos (Le Page-Degivry and Garello, 1992). On the other hand, the addition of physiological concentrations of ABA prevents precocious germination, blocks the expression of germination-specific enzymes, and promotes embryonic development (King, 1982;Triplett and Quatrano, 1982;Black, 1983Black, , 1991Quatrano et al, 1983).…”
mentioning
confidence: 99%
“…Genetic studies have clearly demonstrated a function for ABA in dormancy imposition during seed development (see above discussion) (Karssen and others 1983;Kermode 1995;Bewley 1997;Phillips and others 1997;Foley 2001). Moreover, de novo synthesis of ABA appears to be necessary for dormancy maintenance after seed imbibition, for example, in seeds of sunflower (Helianthus annuus), barley, beechnut, lettuce (Lactica sativa), and Douglas-fir (Pseudotsuga menziesii) (Wang and others 1995;Bianco and others 1997;Le Page-Degivry and others 1997;Le Page-Degivry and Garello 1992;Yoshioka and others 1998). For instance, when tobacco seeds are imbibed, there is an accumulation of ABA in dormant seeds but not in seeds that have been allowed to after-ripen.…”
Section: Post-translational Modification and Protein Degradationmentioning
confidence: 99%
“…The application of carotenoid biosynthesis inhibitors, such as the herbicides norflurazon and FLD (Sanderman and Boger, 1989), often results in a reduction in ABA content as well. FLD treatment results in the precocious gennination of both com and sunflower embryos, and exogenous ABA reverses this effect (Hole et al, 1989;Le Page-Degivry and Garello, 1992).…”
mentioning
confidence: 99%